Heat shock proteins adaptive responses to environmental stressors and implications in health management of decapods - Kifayatullah Mengal; Golara Kor; Pavel Kozák; Hamid Niksirat (Aquaculture Reports, 2023)
Heat shock proteins (HSPs) are highly conserved, cytoprotective proteins, the best know function of which is to facilitate the proper folding of nascent proteins. Environmental stressors, including abiotic and biotic, induce damage to the cell's proteins, activating an adaptive response in any aquatic organism. In response to the stressors, the expression of specific HSP-encoding genes is significantly enhanced across different crustacean species. Functional studies of crustaceans have suggested that HSPs not only mediate chaperone-cytoprotective functions but also activates several innate immune responses. Also, recent studies have suggested that increasing in vivo HSP production via non-lethal heat shock and exogenous HSPs inducing compounds could be an excellent strategy to enhance protective immunity in decapod crustaceans against both abiotic and biotic stresses. Thus, HSPs have great potential as immune booster agents against environmental stressors and their application in farmed and managed decapods could be a significant advancement in reducing stressful conditions to increase their production.